Abandono familiar y estilos de vida de los adultos mayores del distrito de Cachicadán, Santiago de Chuco, 2021 - Tamashiro Cenas, Kiara Naomi (2023)
The present investigation was carried out with the objective of analyzing the influence of family abandonment on the lifestyles of older adults in the district of Cachicadán, Santiago de Chuco, 2021. The sample consisted of a total of 40 older adults in which apply methods such as inductive-deductive; analytical and synthetic statistics; Likewise, the use of techniques such as the interview and survey with their respective instruments such as the interview guide and survey questionnaire. Qualitative and quantitative data were collected in the same district allowing an exhaustive analysis of the variables identified as family abandonment and lifestyles. According to the results obtained, it is affirmed that family abandonment significantly influences the lifestyles of the elderly, since it is identified that most of the variables analyzed are above the means, that is, it has been identified Regarding lifestyles, 75% of older adults present deterioration in their health, 61% of them have economic deprivations, 42% have poor eating habits. Regarding family abandonment, it is evident that 80% have weak family support while 77% have poor communication with their children.